The Imperative in Asy-Syuʹarā’ Chapter: Arabic Rethoric Analysis - Rika Kris Wijayanti (Islah: Journal of Islamic Literature and History, 2022)
This study entitled "ʹAmr in Surah Ash-Syuʹarā' (Maʹani Science Analysis Study)", discusses insyā' ṭalabī ˈamr in surah Ash-Syuʹara'.  The purpose of this study is to find out the forms and meanings of insyā' ṭalabī ʹamr in surah ash-Syu'ara'. The method used is descriptive qualitative, the data is collected through text analysis in surah ash-Syuʹarā'. Then, the data obtained is classified using the maʹani science approach, especially on insyā' ṭalabī ʹamr.  The results of the study found 45 words insyā' ṭalabī ʹamr from 227 verses in surah ash-Syuʹara'. In terms of form, 45 words were found in the form of fi'il ʹamr. In terms of meaning, there are 13 words of hakiki meaning (original meaning), 7 words of do'ā meaning (request), 20 words of irsyād meaning (giving guidance), and 1 word of ihanah wa tahqir meaning (humiliating and belittling), 1 word of ta'dib meaning (educating manners), 2 words of tahqir meaning (belittling), 1 word of tahdid meaning (threatening).